A Novel InSe‐FET Biosensor based on Carrier‐Scattering Regulation Derived from the DNA Probe Assembly‐Determined Electrostatic Potential Distribution. (20th January 2023) - Ji, Hao; Wang, Zhenhua; Wang, Shun; Wang, Chao; Chu, Yujin; Liu, Hong; Zhang, Yu; Han, Lin
Abstract: Low‐dimensional material field‐effect transistor (FET)‐based biosensors have the advantages of high sensitivity, high detection speed, small size, low cost, and excellent compatibility with integrated circuits. The sensing mechanism is extremely important in the design and fabrication of high‐performance FET biosensors in practical applications. Herein, an InSe‐FET biosensor is designed and its dominant sensing mechanism during detection and (mi)RNA detection performance are investigated. Finite element analysis reveals the electrostatic potential distribution in the InSe channel with DNA probe assembly showing that Coulomb scattering is the dominant sensing mechanism for carrier scattering‐sensitive InSe. The simulation and experimental results indicate that carriers in InSe are extremely sensitive to the scattering of surface impurities because of their small electron mass. The firstly reported back‐gate bias working mode of an InSe‐FET biosensor has a linear relationship with an extra‐large detectable range of 1 fM–10 nM, high specificity for identifying 1‐nucleotide polymorphisms, and excellent repeatability and reusability. The detection of biomarker miRNAs in clinical serum samples and specific RNA in SARS‐CoV‐2 pseudovirus samples indicate promising applications of InSe‐FET biosensors in critical disease screening and the fast diagnoses of infectious diseases. This study can be useful for the design and fabrication of high‐performance FET biosensors. Abstract : A novel InSe‐FET biosensor is developed on the basis of carrier‐scattering regulation derived from the DNA probe assembly‐determined electrostatic potential distribution. The InSe‐FET biosensors present a set of high‐performance characters, and the detections of biomarker miRNAs in clinical serum and specific RNA in SARS‐CoV‐2 pseudovirus samples indicate promising applications in critical disease screening and the fast diagnoses of infectious diseases.